Characterization and Imaging of Damage during Creep Crack Growth in 2219 Aluminum Alloy. Issue 1 (1st January 2023) - Guo, Qi; Guo, Zhimin; Fu, Kang; Cao, Yuling; Geng, Xihui; Wang, Xi; Tang, Shengming
Abstract: Aluminum alloys have been extensively applied in aerospace field due to their light weight. Some research results show that creep crack growth is one of the main reasons for the failure of aluminum alloys in high temperature service environment. Micro-CT is a novel method to obtain damage information inside materials, which can quantitatively characterize the volume, quantity and distribution of damage. In this paper, the characterization method based on X-ray micro-CT is utilized to study the growth behavior of damage during creep crack growth of 2219 aluminum alloy. The results indicate that the growth of creep cracks requires the existence of small-volume of damages at the crack tip. And creep crack growth rate in the centre of the sample is greater than that on the surface. The existence of large-volume independent branch cracks creates conditions for the unstable propagation of creep cracks. When the crack grows locally, it does not follow the direction vertical to the stress, but preferentially connects with the surrounding damage. Whereas, the creep crack growth will eventually return to the direction perpendicular to the stress under the influence of stress.